FOLFOXIRI versus FOLFOX or FOLFIRI with targeted therapy in patients with mutant BRAF metastatic colorectal cancer: A systematic review and meta-analysis - M. Yu. Fedyanin; E. M. Polyanskaya; H. H.-M. Elsnukaeva; A. A. Tryakin; I. A. Pokataev; A. A. Bulanov; S. A. Tjulandin (Медицинский совет, 2020)
Introduction. Based on the subgroup analysis of the TRIBE study FOLFOXIRI with bevacizumab is the recommended option for patients (pts) with mBRAF metastatic colorectal cancer (mCRC) in the 1st line. However, subgroup analysis of other studies showed conflicting results. Therefore, we performed systemic review and meta-analysis to compare efficacy FOLFOXIRI and doublets with targeted therapy in pts with mBRAF mCRC in terms of progression free survival (PFS), objective response rate (ORR) and overall survival (OS).Methods. We performed a search of all prospective randomizes studies in PubMed, ASCO and ESMO congresses for all years before May, 2020, compared FOLFOXIRI plus bevacizumab or anti-EGFR antibodies and FOLFOX or FOLFIRI with targeted agents at the 1st line with information of the BRAF status. Primary outcome was hazard ratio (HR) for PFS and 95% confidence interval (CI); secondary – HR for OS and odds ratio (OD) for ORR. Fixed effects were used for analysis. Meta-analysis was conducted by Review Manager Ver. 5.3.Results. We identified 6 trials (CHARTA, STEAM, TRIBE, TRIBE2, VISNU, METHEP2), which included 158 pts with mBRAF (FOLFOXIRI – 82 (52%) and doublets – 76 (48%). According to results of the meta-analysis there was a tendency for higher ORR in pts with FOLFOXIRI (OR 2.07, 95% CI 0.61–7.06; p = 0.24; I2 = 27%, p for heterogeneity 0.26; 3 trials). However we didn’t find any significant improvement in PFS (HR 0.89, 95% CI 0.64–1.23; p = 0.48; I2 = 0%, p for heterogeneity 0.63; 5 trials) or OS (HR 0.9, 95% CI 0.37–1.19; p = 0.048; I2 = 71%, p for heterogeneity 0.06; 2 trials) in the group of triplet.Conclusions. FOLFOXIRI with targeted therapy did not show significant improvement in the PFS and OS in pts with mBRAF compared with FOLFOX or FOLFIRI with targeted antibodies. A prospective randomized trial is needed to determine the optimal chemotherapy regimen at the 1st line for pts with mBRAF mCRC.